2010
DOI: 10.1243/14644193jmbd238
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-static state examination of handle forces and translational acceleration at impending planar motion for the four-caster manually manoeuvred vehicle

Abstract: Motion resistance, handle forces, and translational acceleration of a four-caster manually manoeuvred vehicle (FMV) are examined at impending planar motion.FMV-wheel angular acceleration directions occur in polygon regions of the FMV-body translational acceleration. The mass centre force and torque, which balance motion resistance, using a Coulomb model, are non-linear and discontinuous functions of FMV-body acceleration.The transformation from mass centre force and torque to a dynamically equivalent handlefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Theory predicts substantial variations in motion resistance related to manoeuvring space. 1 This theory is coherent with Health and Safety Laboratory (UK) commentary on operator injury potential when manoeuvring goods vehicles in small spaces 2 and with a patient hoist study 3 which found higher anterior/posterior spinal shear during confined turns.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Theory predicts substantial variations in motion resistance related to manoeuvring space. 1 This theory is coherent with Health and Safety Laboratory (UK) commentary on operator injury potential when manoeuvring goods vehicles in small spaces 2 and with a patient hoist study 3 which found higher anterior/posterior spinal shear during confined turns.…”
Section: Introductionmentioning
confidence: 63%
“…All four-caster vehicle manoeuvres can be usefully represented by 13 manoeuvres distinguished by different centres of zero velocity. 18 These 13 manoeuvres can be visualised using Figure 1(a): the operator manoeuvres the vehicle so that the selected, labelled rod is maintained in the guide-ring centre as the vehicle is turned to face a new direction.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations